(untitled) (Indian Journal of Child Health, 2014)
Background: Necrotizing enterocolitis (NEC) is a neonatal emergency that affects preterm newborns during the 1st weeks of life. Diagnosis is made mainly by clinical criteria since no specific diagnostic tests are available. Objective: The objective was to evaluate fecal calprotectin (fCal) as a biomarker of gut inflammation to predict NEC in preterm neonates. Methods: Design: Diagnostic test evaluation. Inclusion criteria: 102 preterm neonates <36 weeks gestation and within 7 days of birth admitted in Level III neonatal intensive care unit (NICU) were recruited from January 2010 to May 2011. Exclusion criteria: Congenital anomalies and overt infection. Paired stool samples at day 3 and 7 were analyzed by lateral quantum blue rapid calprotectin assay. Cut-off values of fCal were determined among 30 term healthy infants. A structured questionnaire which included gestational age, symptoms at admission, and modified Bell’s staging was used to record NEC episodes on day 3 and 7 of admission. Septic screen and radiological tools were done as per NICU protocol. Results: 48% were above 34 weeks gestation; 31.3% were of very low birth weight. As per modified Bell’s staging on day 3 and 7, 22 and 11 neonates had 1a or above stage, respectively. 15 had features of NEC; of these, 12 were managed appropriately and discharged and 3 died. In the receiver-operated curve with fCal >279 ?g/g as cutoff, the area under the curve was 0.652 (95% confidence interval: 0.516-0.789). Day 3 fCal levels were high in 65.7% neonates. Using NEC as outcome, sensitivity of the test was 93.3%; specificity was 39%; positive predictive value was 20.8% and negative predictive value was 97.14%. Conclusion: fCal has high sensitivity for diagnosing NEC in preterm neonates. However, further research is needed to establish its clinical usefulness.